MODEL QUANTUM TEACHING MENGGUNAKAN MEDIA GAMBAR SERI TERHADAP HASIL BELAJAR BAHASA INDONESIA KELAS V SD NEGERI KURIPAN WONOSOBO - Fajar Cahyadi; Pujiyati Pujiyati (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2013)
?é?áThe problems revealed in this research is whether there is influence of Quantum Teaching Model by using Media of Picture Series toward Learning Outcomes Indonesian course of the fifth Grade in Kuripan State Elementary School"? Collecting data in this research conducted using tests and non-test. The data obtained in tests using normality test, homogeneity test and hypotheses test. Once the analysis was performed using t test analysis. Analysis of the early stages of the pre-test values, indicating that the two groups of normally distributed and homogeneous. After the second group was given a different treatment, the experimental group applied using a model of Quantum Teaching learning to use the media picture series and applied learning control group using a conventional lecture method. Gained an average for the experimental group was 74.5 and the average for the control group was 69.0. Hypothesis testing using t-test found 2,848, while 2,042 worth. This indicates acceptable Ha Ho is rejected because>. The conclusion from this study is that there is a positive effect of giving Quantum Teaching learning model using the media picture series against Indonesian student learning outcomes, as seen from the average results of the experimental group learned better than the control group.